PENYUSUNAN KETERANGAN PEMERINTAH ATAS PENGUJIAN UNDANG-UNDANG TERHADAP UNDANG UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - ., Qomaruddin (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
“In order to carry out the duties and functions of the Minister ofLaw and Human Rights Republic of Indonesia as the President’spermanent proxy in any Judicial Reviews before theConstitutional Court, the Directorate Litigation of Legislationas an echelon unit II in Directorate General of Legislation, amongothers, prepares and composes the Government’s/President’sOpinion and provides assistance in any trials before theConstitutional Court. The activities in preparing and composingthe Government’s Opinion is started from analysing the supply,collecting data, coordinating with the related institution in anyJudicial Reviews and also the concept of composing theGovernment’s Opinion and Opening Statement. Because of thePresident’s Opinion is a formal Government’s Opinioncomposed in oral and written concern about the principal ofsuplication which is the result of coordination between ministersor Government’s Institution, then in composing the government’sOpinion, Directorate Litigation of Legislation coordinates withDepartments, State Agencies, Non-Department GovernmentAgencies, community organizations, religion organizations, orprofessional organizations and invites sources from academics,practical, professional and NGOs to find any supports orinformation related with the supply principals.”